2017
DOI: 10.18632/oncotarget.23532
|View full text |Cite
|
Sign up to set email alerts
|

Stroma-derived extracellular vesicles deliver tumor-suppressive miRNAs to pancreatic cancer cells

Abstract: The biology of tumor-associated stroma (TAS) in pancreatic ductal adenocarcinoma (PDAC) is not well understood. The paradoxical observation that stroma-depletion strategies lead to progression of PDAC reinforced the need to critically evaluate the functional contribution of TAS in the initiation and progression of PDAC. PDAC and TAS cells are unique in their expression of specific miRNAs, and this specific miRNA expression pattern alters host to tumor microenvironment interactions. Using primary human pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Although miR-145 serves crucial roles in the development of cancer, the majority of studies have focused on the original cells, and the expression of miR-145 in exosomes and its effect on OC remains largely unknown. However, one previous study revealed that the exposure of pancreatic ductal adenocarcinoma to miR-145-5p-enriched tumor-associated stroma exosomes cells decreased cell viability in a dose-dependent manner ( 32 ). To the best of our knowledge, the present study is the first to demonstrate the significant downregulation of miR-145-5p expression in OC exosomes, indicating that the enhanced secretion of miR-145 via exosomes may be an underlying approach to treating OC ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although miR-145 serves crucial roles in the development of cancer, the majority of studies have focused on the original cells, and the expression of miR-145 in exosomes and its effect on OC remains largely unknown. However, one previous study revealed that the exposure of pancreatic ductal adenocarcinoma to miR-145-5p-enriched tumor-associated stroma exosomes cells decreased cell viability in a dose-dependent manner ( 32 ). To the best of our knowledge, the present study is the first to demonstrate the significant downregulation of miR-145-5p expression in OC exosomes, indicating that the enhanced secretion of miR-145 via exosomes may be an underlying approach to treating OC ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28 mL of conditioned medium was used for exosome preparation after 24 h of incubation. Exosomes were isolated from these conditioned culture media using the ultracentrifugation/ultrafiltration protocol were previously established . Briefly, conditioned culture media were centrifuged at 2000 × g for 30 min to clear dead cells and cell debris.…”
Section: Methodsmentioning
confidence: 99%
“…EV-miR-143 from normal epithelial prostate cells suppresses the proliferation of adjacent prostate cancer cells [143]. EV-miR-145 from tumor-associated stroma cells impairs the viability and induces the apoptosis of adjacent pancreatic ductal adenocarcinoma cells [144]. EV-miRNAs from liver stem cells inhibit the proliferation and promote the apoptosis of hepatocellular carcinoma (HCC) cells in vitro and in vivo [145].…”
Section: Regulation Of Malignant Phenotypes Of Cancer Cells By Tumor mentioning
confidence: 99%